On the subject of the effectiveness of the ATC and pilot joint simulation training (retraining) program - Stepnova, A. I.; Kochergin, V. I.; Stepanov, S. M.; Borsoev, V. A. (Nauchnyĭ vestnik MGTU GA (Online), 2022)
The purpose of the article is to conduct a statistical data analysis obtained after the experimental study. The experimental research deals with rating the trainees’ level of proficiency before and after the proposed method of the ATC and pilot joint training (retraining). It’s common knowledge that progress in aviation has moved far forward. The fourth, fifth and sixth-generation aircraft have come into existence. Aircraft and automated systems have become digital. In order to develop and implement ATM systems, ICAO has identified three fundamental concepts that will allow us to enhance human reliability in the future. One of the concepts is human-oriented automation. Automation involves the transition from the analog onboard and ground systems to digital ones. As a result, the onboard and ground systems, after modernization, will receive the fifth and sixth-generation abbreviation. Subsequently, a new approach will be required to train (retrain) air traffic controllers and pilots to operate these systems. To solve this problem, it is necessary to change the concept of training flight and traffic control personnel. The article provides an evaluation of the proposed new technique for the joint training (retraining) of ATC and pilots by conducting a statistical analysis of experimental data. The proposed training method will enable us to improve the quality of training, reduce a number of pilot and ATC errors, which are the underlying principles of the ICAO concept. The article presents the statistical analysis of data based on the Student t-criterion and the law of random variables distribution, which will make it possible to draw a conclusion about the effectiveness of the proposed method for training specialists.